A Pengaruh Keikutsertaan Program Pengelolaan Penyakit Kronis Terhadap Kendali Glukosa Darah Pasien Diabetes Melitus Tipe 2 Di Cabang Pematangsiantar : Pengaruh Keikutsertaan Program Pengelolaan Penyakit Kronis Terhadap Kendali Glukosa Darah Pasien Diabetes Melitus Tipe 2 Di Cabang Pematangsiantar - Kiki Christmar Marbun; Firdauz Hafidz As Shidieq (BPJS Kesehatan, 2023)
DM Type 2 is a chronic disease and Indonesia is ranked 7th in the world. This situation causes health burden, both economically and disability. The Disease Management Program was developed to control patient health status and control costs. Prolanis is a form of disease management program organized by BPJS Kesehatan. The purpose of this study was to analize impact of Type 2 DM Prolanis on controlling blood glucose levels in patients. This is a quantitative study with a crosssectional design by comparing Type 2 DM patients who participate in Type 2 DM Prolanis with those who do not take part in the program at 15 target FKTPs in the region of Pematangsiantar branch of BPJS Kesehatan. Using secondary data which was conducted retrospectively in 2021 involving 717 respondents.The majority of respondents were participants I Type 2 DM Prolanis (70,29%), aged 56 years and over, female (57,34%), high school educated (39,47%), coming from the BP segment (retirement) (40o.44%). Have followed Type 2 DM Prolanis for more than 6 months (more than 85 % of respondents), and actively visited FKTPs for more than 3 times during the period of January to December 2021.